Tanggung Jawab Notaris Terhadap Kewajibannya Dalam Hal Pembacaan Akta - Iqbal Putra Pratama; Fifiana Wisnaeni; Irma Cahyaningtyas (Magister Kenotariatan Universitas Diponegoro, 2021)
Notaries as public officials who are authorized to make authentic deeds also have obligations, one of which is to read the deed in front of the audience. The research method used in this article is normative research. The result of the discussion of this article is that the Notary is responsible for the deed he makes, starting from the making, reading to signing, the reading of the deed must be carried out by the Notary even though the Notary has attribution authority and can delegate it to staff but the deed read by the staff can be considered null and void. The conclusion of this article is that the reading of the deed must be carried out by the Notary Public, the Notary's responsibility if the deed is read by the staff, namely receiving administrative sanctions or sanctions from the Notary's code of ethics and if there is an error that harms the parties, the Notary is liable in civil terms by compensating for losses.Keywords: notary; responsible; reading of the deedAbstrakNotaris sebagai pejabat umum yang berwenang untuk membuat akta autentik juga mempunyai kewajiban salah satunya yaitu pembacaan akta dihadapan penghadap. Metode penelitian yang digunakan artikel ini adalan penelitian normatif. Hasil pembahasan artikel ini yaitu Notaris bertanggung jawab atas akta yang dibuatnya mulai dari pembuatan, pembacaan sampai dengan penandatanganan, pembacaan akta wajib dilakukan oleh Notaris meskipun Notaris mempunyai kewenangan atribusi dan bisa melimpahkan ke staf tetapi akta yang dibacakan oleh staf bisa dianggap batal demi hukum. Simpulan dari artikel ini yaitu pembacaan akta wajib dilakukan oleh Notaris, tanggung jawab Notaris jika akta dibacakan oleh staf yaitu menerima sanksi administratif atau sanksi dari kode etik Notaris dan jika terdapat kesalahan yang merugikan para pihak maka Notaris bertanggung jawab secara perdata dengan mengganti kerugian.Kata Kunci: notaris; tanggung jawab; pembacaan akta